ТӨВД СУРВАЛЖ ДАХЬ ЦОГТ ХУН ТАЙЖИД ХОЛБОГДОХ МЭДЭЭ - Д.Бүдсүрэн, (Acta Mongolica, 2010)
The yellow section of the Tibetan religion widely spread into Mongolia in the 17th and 18th centuries and under its influence the Mongolian learned people wrote their books in Tibetan. In the report we intended to write about the information and facts related to Tsogt khun taij mentioned in the Tibetan sources. So we first chose the works written by the Mongols in Tibetan. We made the following conclusions on the unformation mentioned in the Tibetan sources: 1 .Tsogt khun taij is a grandson of Onokhui uizen noyon who was the son of Gersenz, the youngest son of Batmunkh dayan khan. 2. He was exiled from the land of Khalkh and came to the lake of Khukh nuur. 3. He, who made the damage to the yellow religion was defeated by Guush khan.